Eksplorasi Peran Kepemimpinan Transformasional dalam Mendorong Inovasi Organisasi - Yusuf Rahman Al Hakim; Dwi Simbe Sagita; Mochamad Irfan (Jurnal Syntax Admiration, 2024)
In an era of globalization and increasingly fierce competition, innovation is key for organizations to remain relevant and competitive. Innovation enables organizations to develop new products and services, improve process efficiency, and create new value for customers. The aim of this research is to explore the role of transformational leadership in driving innovation in organizations. This research adopts qualitative research methods, where data collection techniques are carried out through literature studies. After the data is collected, the analysis is carried out through three stages, namely data reduction, data presentation, and conclusions. Transformational leaders play an important role in articulating a clear vision, building an organizational culture that supports experimentation and risk-taking, and providing strong support to employees to innovate. By demonstrating characteristics such as trust, integrity, and concern for the needs and aspirations of team members, transformational leaders create work environments that allow creative ideas to flourish and be implemented.